Upaya Kepolisian Dalam Menanggulangi Tindak Pidana Penyalahgunaan Narkotika Di Wilayah Kabupaten Sambas - Dewi, Anugerah; Anshari, Ashari; Lestari, Nina Niken (Res Judicata, 2024)
The advancement of time brings more complex challenges, including the circulation of narcotics. Narcotics abuse has become an increasingly serious issue in many areas of Indonesia. This phenomenon occurs not only in major cities but also in regions such as Sambas Regency. This research aims to examine the efforts made by the police to combat narcotics abuse in the Sambas Regency area and to identify the obstacles faced by the police in tackling narcotics abuse. This study uses a qualitative approach with descriptive analysis, utilizing primary data obtained through direct interviews and secondary data gathered from literature sources. The results of this study indicate that the police efforts in combating narcotics abuse in Sambas Regency include pre-emptive, preventive, repressive actions, as well as rehabilitation and guidance. The obstacles faced by the police include internal challenges such as limited personnel, inadequate facilities and infrastructure, difficulty in obtaining strong physical evidence, and challenges in legal proof. External factors from the environment and society include limited public information and participation, environmental influences, geographical factors, and uneven dissemination of education and outreach programs.